2019
DOI: 10.1002/adfm.201905252
|View full text |Cite
|
Sign up to set email alerts
|

Regulating the Electronic Structure of CoP Nanosheets by O Incorporation for High‐Efficiency Electrochemical Overall Water Splitting

Abstract: The exploration of earth‐abundant and high‐efficiency bifunctional electrocatalysts for overall water splitting is of vital importance for the future of the hydrogen economy. Regulation of electronic structure through heteroatom doping represents one of the most powerful strategies to boost the electrocatalytic performance of hydrogen evolution reaction (HER) and oxygen evolution reaction (OER). Herein, a rational design of O‐incorporated CoP (denoted as O‐CoP) nanosheets, which synergistically integrate the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
136
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 252 publications
(138 citation statements)
references
References 52 publications
2
136
0
Order By: Relevance
“…[ 29 ] Additionally, 2D nanomaterials, for example, nanosheets, characteristics of large surface area and rich exposed edge active sites as well as large contact area with the electrolyte for fast interfacial charge transport, are widely designed and prepared for promising electrocatalysts. [ 30–36 ] The ultrathin 2D nanomaterials can achieve over 40 times higher electrocatalytic activity than its bulk counterpart. [ 37 ] Xie's group has demonstrated that the electrocatalytic performance is largely dependent upon the thickness of 2D nanomaterials by enhancing electrical conductivity, varying exposure to coordinately unsaturated surface atoms and shortening the ion diffusion paths.…”
Section: Introductionmentioning
confidence: 99%
“…[ 29 ] Additionally, 2D nanomaterials, for example, nanosheets, characteristics of large surface area and rich exposed edge active sites as well as large contact area with the electrolyte for fast interfacial charge transport, are widely designed and prepared for promising electrocatalysts. [ 30–36 ] The ultrathin 2D nanomaterials can achieve over 40 times higher electrocatalytic activity than its bulk counterpart. [ 37 ] Xie's group has demonstrated that the electrocatalytic performance is largely dependent upon the thickness of 2D nanomaterials by enhancing electrical conductivity, varying exposure to coordinately unsaturated surface atoms and shortening the ion diffusion paths.…”
Section: Introductionmentioning
confidence: 99%
“…However, because of the sluggish reaction kinetics and non-negligible overpotential (η) for both hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) during water electrolysis [5][6][7][8], the large-scale H 2 preparation is seriously restricted, which has driven the exploration of high-efficiency electrocatalysts. Nowdays, the most widely used electrocatalysts for HER and OER are noble metals and their oxides, such as platium (Pt) [9,10], iridium (Ir) [11,12], iridium dioxide (IrO 2 ) [13,14] and ruthenium (Ru) [15][16][17]. Unfortunately, the scarcity and high-costs hinder their industrial applications.…”
Section: Introductionmentioning
confidence: 99%
“…The performance for the NiCo-CeO 2 ||NiCo(OH) x -CeO 2 electrolyzer also outperforms most recently reported electrolyzers based on non-noble bifunctional electrocatalysts (Figure 5e; Table S4, Supporting Information). [45][46][47][48][49][50][51][52][53][54][55][56][57][58][59] The excellent overall water splitting activity of the NiCo-CeO 2 ||NiCo(OH) x -CeO 2 electrolyzer is not only attributed to the high intrinsic catalytic activities of NiCo-CeO 2 / GP and NiCo(OH) x -CeO 2 /GP, but also to the self-supported electrode structure. Due to the in situ growth of active species on conductive substrate, the interface resistances of the self-supported NiCo-CeO 2 /GP and NiCo(OH) x -CeO 2 /GP electrodes are greatly lower than those of the Pt/C(20%)/GP and RuO 2 /GP electrodes by physically coating (Figure S25, Supporting Information), which are conducive to the rapid electron transfer.…”
Section: Resultsmentioning
confidence: 99%
“…The performance for the NiCo–CeO 2 ||NiCo(OH) x –CeO 2 electrolyzer also outperforms most recently reported electrolyzers based on non‐noble bifunctional electrocatalysts (Figure 5e; Table S4, Supporting Information). [ 45–59 ]…”
Section: Resultsmentioning
confidence: 99%